Dampak Kebijakan Publik Terhadap Resiliensi dan Eskalasi UMKM di Kota Makassar: Studi Kebijakan Afirmatif, Transformasi Spasial, dan Digitalisasi Ekonomi (2020–2025) - Muhammad Nasir (Fakultas Ekonomi dan Bisnis, 2025)
Abstract This study evaluates the strategic impact of the Makassar City Government's policies on the Micro, Small, and Medium Enterprises (MSME) ecosystem during the 2020–2025 period. Using a public policy analysis approach and regional economic empirical data, this study examines the effectiveness of the paradigm shift from supply-side interventions to demand-side interventions, as well as the integration of the Smart City concept in local economic empowerment. Key findings indicate that affirmative policies allocating 50% of the regional budget (APBD) and the Local E-Catalogue successfully created a significant captive market for formal MSMEs. The